Unveiling the prevalence of invasive alien plant species in multiple-use zone of Initao-Libertad Protected Landscape and Seascape, Misamis Oriental, Philippines - LARRY C. HERBITO JR.; JAIME Q. GUIHAWAN; CHRISTINE MARIE V. CASAL; DAISY LOU L. POLESTICO; ARMI G. TORRES (Society for Indonesian Biodiversity, 2024)
Abstract. Herbito Jr. LC, Guihawan JQ, Casal CMV, Polestico DLL, Torres AG. 2024. Unveiling the prevalence of invasive alien plant species in multiple-use zone of Initao-Libertad Protected Landscape and Seascape, Misamis Oriental, Philippines. Biodiversitas 25: 3286-3294. Invasive Alien Plant Species (IAPS) threaten Protected Areas (PAs) globally, causing habitat degradation, biodiversity reduction, and ecosystem disruption. In the Philippines, data on invasive species in PAs is limited. This study aimed to investigate the prevalence, abundance, and diversity of IAPS in multiple-use zone of Initao-Libertad Protected Landscape and Seascape (ILPLS), Misamis Oriental, Philippines. Using belt-transect method, a total of 15 nested plots (20×20 m for trees, 5×5 m for herbs and shrubs, and 1×1 m for grasses and lianas) were established. Twenty-nine plant species from 18 families were identified, comprising 18 Native Species (NS), seven Non-Invasive Alien Species (NIAS), and four IAPS. The IAPS identified were Gmelina arborea, Leucaena leucocephala, Lantana camara, and Swietenia macrophylla which had the highest relative abundance of 96.83%. The Shannon-Weiner diversity indices showed very low to low diversity of 0.30 to 2.17, and an unbalanced to semi-balanced species evenness of 0.17 to 0.70. The Wilcoxon signed-rank test showed a significant difference in relative abundance between NS and IAPS (p = 0.01576). The Wilcoxon rank-sum test indicated significant differences in species diversity and evenness of p = 0.03359 and 0.03343, respectively. These findings are crucial for developing IAPS control strategies in the ILPLS in the future.